A Research Study on Foreign Language Anxiety and Self-efficacy among EFL Learners in Chinese University Students - Gao, Xiaohan; Yu, Qing; Zhong, Meiyuan (Transactions on Social Science, Education and Humanities Research, 2024)
Emotion and self-efficacy are both essential elements in learning the English language. It is critical to examine the function of anxiety and self-efficacy in English as a foreign language learning, as well as the interaction between these two elements. This study evaluated the correlation between foreign language anxiety and self-efficacy across Chinese university students and explored whether these factors differed according to different majors. 162 Chinese university students were involved in a questionnaire survey, and four of them were interviewed. The main findings were: (1) the majority of university students had moderate levels of self-efficacy and anxiety; (2) there was no significant relationship between participants’ self-efficacy and anxiety; and (3) there were significant disparities between participants’ self-efficacy and foreign language anxiety across different majors. These findings not only further confirm the significance of anxiety and self-efficacy in EFL learning but may also provide implications for Chinese university students to relieve anxiety and increase self-efficacy so that appropriate coping strategies can be adopted.